[5x. + y =39
[x. - y =3
vc podem me ajudar pf
Soluções para a tarefa
Respondido por
1
Resposta:
x = 6 y = 3
Explicação passo-a-passo:
o próprio sistema já anula o y então:
5x + y = 39
x - y = 3
6x = 36
x = 36/6
x=6
6 - y = 3
-y = 3 - 6 = -3
-y = -3 .(-1)
y = 3
bons estudos!!!
paulodejesuscombr34:
ajudou muito
Perguntas interessantes
Informática,
5 meses atrás
Pedagogia,
5 meses atrás
História,
5 meses atrás
Geografia,
8 meses atrás
História,
8 meses atrás
Química,
11 meses atrás
Pedagogia,
11 meses atrás
Matemática,
11 meses atrás